Enhancing pig productivity on East African smallholder farms - Carter, Natalie A. (University of Guelph, 2015)
East African smallholder farmers raise pigs to generate income for medicine, school, food, and funerals (Dewey et al. 2011). Seasonal feed shortages and unbalanced diets contribute to slow pig growth and reduced earnings. The thesis objectives were to: 1) determine the average daily gain (ADG) of pigs on Kenyan smallholder farms; 2) estimate east African pigs’ nutrient requirements; 3) develop low-cost diets based on nutritional value and seasonal availability of east African pig feedstuffs; and 4) compare pen-and pig-level productivity (ADG, feed conversion, impact of starting bodyweight [SBW]) of Ugandan local and crossbreed pigs fed commercial versus forage- or silage-based diet. Factors associated with ADG of pigs weighed during a cross-sectional, observational study were determined using linear models. Feedstuff nutrient composition was estimated through nutrient analysis and from literature. Tropical-pig performance results were used to adjust the NRC (2012) growing-finishing-pig nutrient requirement model and estimate east African pigs' nutrient requirements. Diets were generated using a least-cost diet-formulation program. Pen- and pig-level productivity of Ugandan pigs fed 1 of 3 randomly assigned diets (commercial, forage-based, or silage-based) were assessed using linear and mixed linear regression models, respectively. Kenyan pigs had low ADG (0.13±0.002 kg/day). The ADG of 3- and 10- to 12-month-old pigs (0.12±0.005 and 0.11±0.005 kg/day, respectively) was lower than that of 1-to 2-month-old pigs (0.13±0.007 kg/day) (p<0.05). Assuming a 1kg birthweight ADG can be estimated with pigs' weight and age. Nutritionally suitable pig feedstuffs available in 3 seasons are most limited from November-February. High ash content in sampled milled feeds versus the literature suggests contamination. For every 1kg increase in SBW, ADG increased by 0.012, 0.015, 0.013, and 0.009 kg/day in 9-15, 15-19, 20-24, and 28-32-week-old pigs, respectively. Feed conversion was similar to that of other tropical pigs. Newly-weaned pigs fed forage- and silage-based diet had lower ADG (0.27±0.013 and 0.25±0.013 kg/day less, respectively) than pigs fed commercial diet. Forage- and silage-based diets are unsuitable for small newly-weaned pigs but are useful for heavier pigs (11.9 and 9.2 kg SBW, for forage- and silage-based diet, respectively) and ensure an ADG higher than that of pigs on Kenyan smallholder farms.